The Leadership of the Role Head of Madrasah in Improving the Quality of Islamic Religious Education Teachers - Mitha Shaskila Sinaga; Tasman Hamami (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2026)
Improvements in the quality of education in madrasahs are significantly influenced by the quality of human resources, particularly PAI teachers, who play a crucial role in shaping the character, morals, and spirituality of students. However, in practice, improving the quality of PAI teachers still faces various challenges, requiring effective and professional leadership from madrasah principals. This study aims to examine the role of madrasah principal leadership in improving the quality of PAI teachers, assess the effectiveness of implementing this role, and identify the supporting and inhibiting factors. This study uses a literature review method by analyzing various literature relevant to educational leadership and teacher quality improvement. The results show that madrasah principals perform seven main roles known by the acronym EMASLIM, namely educator, manager, administrator, supervisor, leader, innovator, and motivator. Among these roles, the functions of educator, manager, supervisor, and motivator have the most direct influence on improving the quality of PAI teachers. Effective madrasah leadership contributes significantly to improving teacher professionalism, both in terms of pedagogical, professional, social, and personality competencies. The quality of PAI teachers is influenced by internal factors, such as talent, interest, and educational background, as well as external factors, such as the availability of facilities and infrastructure and participation in training programs. Therefore, madrasah principals are expected to be able to implement innovative and sustainable leadership strategies to create a work environment conducive to teacher professional development and improve the quality of madrasah education.